The Utilization of Social Media as a Digital Marketing Tool to Improve the Performance of MSMEs: A Literature Study - Elizabeth Natalia Christien Wijaya; Aris Eddy Sarwono; Sinta Putriana (CV. Publikasi Indonesia, 2026)
The rapid growth of social media has fundamentally transformed digital marketing strategies, particularly for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This study aims to analyze the benefits of social media as a digital marketing tool and its impact on MSME performance through a systematic literature review approach. Using qualitative methods, this research examined 25 scientific publications published between 2019 and 2024, supplemented by observational analysis of Instagram and TikTok analytics data, as well as survey results from MSME practitioners. The findings reveal that social media utilization—particularly through Instagram and TikTok—significantly contributes to increased brand awareness, expanded customer reach, increased sales volume, and reduced marketing costs for MSMEs. Instagram demonstrates strengths in visual brand storytelling and community engagement, while TikTok shows superior performance in organic reach and viral content distribution, particularly among younger demographic groups. MSMEs that actively manage social media platforms report an average revenue increase of 23–47% within the first year of adoption. However, several challenges remain, including limited digital literacy, inconsistent content management practices, and the absence of structured performance measurement frameworks. This study contributes a practical framework for MSME social media marketing by bridging theoretical perspectives with empirical evidence from the Indonesian market context.